Integrating Livestock into Agricultural Systems for Increased Livestock Productivity in Tanzania - International Institute of Tropical Agriculture; International Livestock Research Institute (International Food Policy Research Institute, 2021)
This dataset is generated from the study conducted to evaluate the impact of improved Napier grass and maize stover based diets on milk yield under smallholder conditions. Farms were used as experimental units and lactating cows were used as replicates. 23 farmers from six villages participated in the trial. 24 lactating cows with two genotypes (local and improved cattle) were selected and were fed with Napier grass or maize stover based diets supplemented with bean haulms at different levels (100, 80, 70, and 60%). Data were collected for 45 days with a 7-day adjustment. Data included information on breed type, fodder, supplementation type, pre-study fodder type, milk production, lactation length, source of feed, and feed and water intake among others.